Influence of cultivation conditions on the bioenergy potential and bio-compounds of Chlorella vulgaris. (February 2020) - Caetano, N.; Melo, A.R.; Gorgich, M.; Branco-Vieira, M.; Martins, A.A.; Mata, T.M.
Abstract: This study aims to evaluate the influence of cultivation conditions on the bioenergy and high value biocompounds contents of Chlorella vulgaris . Results show that the use of nitrate rich media, from 170.7 mg/L, favors a faster biomass growth, reaching values above 800 mg/L biomass. In addition, it favors higher pigments concentrations with more emphasis for the cultures with a nitrate concentration of 569 mg/L, where chlorophyll-a and carotenoids reached maximum concentrations of 6 and 2 mg/L, respectively. As regards the lipid content, nitrate deprivation (<28.4 mg/L) favors the accumulation of lipid content by microalgae (around 42%). The use of media with lower iron concentrations (0.5 mg/L) was favorable for obtaining biomass with higher concentrations of chlorophyll-a, at an initial stage, with values varying from 0.2 to 0.6 mg/L. In the tests carried out under mixotrophic conditions (addition of glucose), it was observed that contamination occurred in all the cultures, possibly due to the high concentration of carbon source that had values between 0.5 and 1.5 g/L of glucose, and consequently, growth decreased.